Analisis Perubahan Penggunaan Lahan pada Area Sekitar Stasiun Bandar Khalipah Kabupaten Deli Serdang Sumatera Utara - Sugianto; Hadinugroho, Dwi Lindarto; Thoha, Achmad Siddik (Jurnal Serambi Engineering, 2025)
Sustainable urban planning requires the integration of land use and transport to create efficient, safe and sustainable areas. One approach that supports this is the impact of regional development due to station operations, as illustrated by land use change. This research aims to analyse the land use change around Bandar Khalipah Station in Deli Serdang Regency as a potential area for TOD development in the future. This research uses visual interpretation method to classify land use using Google Earth satellite images in the period of 2014, 2018 and 2024. Data analysis was conducted by analysing the land use area and land use change matrix in the period of 2014 - 2024. The results of this study showed that there were changes in land use from the period 2024 - 2024. Land use in the area around Bandar Khalipah Station consists of six types, namely public areas and green open spaces, station and railway areas, commercial areas, offices, settlements and roads. Land change in 2014-2024 is most dominant in public areas and green open spaces. Public areas and green open spaces experienced a decrease in area due to land change into commercial and residential areas, so these two land categories experienced a significant increase in area.